Cognition in ALS and the overlap with frontotemporal dementia (FTD) - Bak, Thomas (Henry Stewart Talks, 2016)
Cognition & behavioural deficits in ALS, Dementia associated with ALS, Language, cognition & behaviour in MND, Onset vs. progression of ALS, Why cognition is affected in ALS, Assessment of cognitive symptoms in ALS (ECAS)
Reviewed at 2022/05/04